Antibody repertoire: embracing diversity. - Pollard, A; Hill, A (2011)
In this Perspective, we discuss two papers that show that the breadth of the antibody response to vaccines could be manipulated by the use of particular vaccine adjuvants that stimulate innate immune mechanisms. The ability to increase the repertoire of antibodies induced by a vaccine may help to control variable pathogens that alter their exposed antigens to evade the immune system.